2018
DOI: 10.18632/oncotarget.24836
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new B-ALL cell line with constitutional defect of the Notch signaling pathway

Abstract: Notch signaling contribution to B-cell acute lymphoblastic leukemia (B-ALL) development is still under investigation. The serendipitous onset of B-ALL in a patient affected by the germinal Notch mutation-dependent Alagille syndrome allowed us to establish a B-ALL cell line (VR-ALL) bearing a genetic loss of function in components of Notch signaling. VR-ALL is a common-type B-ALL cell line, grows in conventional culture medium supplemented with 10% serum, and gives rise, once injected into immunodeficient NOG m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…B-ALL cell lines including VR-ALL, RS4;11, and SUP-B15 were cultured in complete RPMI (RPMI supplemented with 10% FBS, 1% L-glutamine, and 1% penicillin/streptomycin). VR-ALL cells were isolated, characterized, and validated in our laboratory, as previously described (15), whereas RS4;11 and SUP-B15 cell lines were acquired from ATCC. Stability and identity of all B-ALL cell lines were controlled during and at the end of the current study using flow cytometry of membrane marker, morphologic analysis after Giemsa staining (15), and short tandem repeat (STR).…”
Section: Cell Line Culture and Validationmentioning
confidence: 99%
See 3 more Smart Citations
“…B-ALL cell lines including VR-ALL, RS4;11, and SUP-B15 were cultured in complete RPMI (RPMI supplemented with 10% FBS, 1% L-glutamine, and 1% penicillin/streptomycin). VR-ALL cells were isolated, characterized, and validated in our laboratory, as previously described (15), whereas RS4;11 and SUP-B15 cell lines were acquired from ATCC. Stability and identity of all B-ALL cell lines were controlled during and at the end of the current study using flow cytometry of membrane marker, morphologic analysis after Giemsa staining (15), and short tandem repeat (STR).…”
Section: Cell Line Culture and Validationmentioning
confidence: 99%
“…VR-ALL cells were isolated, characterized, and validated in our laboratory, as previously described (15), whereas RS4;11 and SUP-B15 cell lines were acquired from ATCC. Stability and identity of all B-ALL cell lines were controlled during and at the end of the current study using flow cytometry of membrane marker, morphologic analysis after Giemsa staining (15), and short tandem repeat (STR). The stability and identity of all other cell lines (including HEK 293, HEK 293T, CEM, and Ramos) used as control in Western immunoblot were validated only through flow cytometry of membrane marker and morphologic analysis after Giemsa staining.…”
Section: Cell Line Culture and Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, NOTCH/JAG1 signaling resulted in playing a fundamental role in MSC-dependent control of tumor initiation, growth, and chemoresistance. JAG1 overexpression has been shown to induce AML in mice [100], whereas NOTCH1, JAG1, and the main Notch target gene HES1 are overexpressed in AML-MSCs thus promoting survival of tumor cells exposed to chemotherapeutic agents [101] (Figure 2). Several studies have demonstrated that the tumor BM milieu is sufficient to convert a healthy BM stroma into a tumor supporting microenvironment.…”
Section: Mscs In Hematological Malignanciesmentioning
confidence: 99%